Analysis of Qur'anic Verses Regarding the Hijab and the Adoption of the Clean Style Hijab in the Post-Modern Era - Asyari, Muhammad Ma’ruf; Muzaini, Ahmad; Mailani, Leni (UIN Mataram, 2024)
In the late 1990s, the term jilbabers emerged, referring to individuals who consistently wore the hijab in their daily lives. The lifting of the ban on the hijab in the 1980s marked a significant turning point, providing an opportunity for society to explore various styles of the hijab, including the kerudung gaul and celebrity-style hijab. Over time, the hijab among Muslim women in Indonesia has evolved beyond its role as a modest covering to become a widely popular fashion trend. This study focuses specifically on the clean style hijab, characterised by a simple back-tie fastening. The primary aim of this research is to contribute to the scholarly understanding of this phenomenon, particularly in the fields of social, cultural, and religious studies. Using a qualitative approach through a literature review, this study seeks to explore the extent to which this particular hijab style influences social and cultural dynamics and to provide insights into the development of fashion trends within the Muslim community. The research methodology involves an in-depth analysis of relevant literature, historical documents, and cultural artifacts related to the evolution of hijab styles in Indonesia. This approach enables a comprehensive understanding of the societal shifts and cultural implications associated with the adoption of the clean hijab style. It is hoped that the findings of this research will not only deepen the understanding of the transformation in hijab usage but also offer practical contributions to enriching the social and cultural life of the Muslim community in Indonesia. Abstrak: Pada akhir tahun 1990-an, istilah jilbabers mulai dikenal, merujuk pada individu yang secara konsisten mengenakan jilbab dalam kehidupan sehari-hari. Keputusan untuk mencabut larangan jilbab pada tahun 1980-an menjadi titik balik yang penting, membuka ruang bagi masyarakat untuk mengeksplorasi berbagai gaya jilbab, termasuk kerudung gaul dan jilbab gaya selebritis. Seiring berjalannya waktu, jilbab di kalangan perempuan Muslim Indonesia tidak hanya berfungsi sebagai penutup aurat, tetapi juga berkembang menjadi elemen mode yang sangat populer. Penelitian ini memfokuskan perhatian pada gaya jilbab clean atau pengikatan ke belakang. Tujuan utama dari penelitian ini adalah memberikan kontribusi terhadap pemahaman ilmiah, khususnya dalam bidang studi sosial, budaya, dan agama. Dengan menggunakan pendekatan kualitatif melalui studi pustaka, penelitian ini bertujuan untuk mengeksplorasi sejauh mana model jilbab tersebut mempengaruhi dinamika sosial dan budaya serta memberikan wawasan tentang perkembangan tren mode di kalangan masyarakat Muslim. Metode penelitian yang digunakan adalah analisis mendalam terhadap literatur yang relevan, dokumen sejarah, serta artefak budaya yang berkaitan dengan evolusi gaya jilbab di Indonesia. Pendekatan ini memungkinkan pemahaman yang lebih komprehensif mengenai perubahan sosial dan implikasi budaya terkait dengan adopsi gaya jilbab clean. Diharapkan, hasil penelitian ini tidak hanya memperdalam pemahaman mengenai transformasi penggunaan jilbab, tetapi juga memberikan kontribusi praktis yang dapat memperkaya kehidupan sosial dan budaya masyarakat Muslim di Indonesia.